Pengelolaan Eco enzyme Menjadi Produk Bernilai Ekonomis: Peluang Pengembangan Usaha Mandiri untuk Warga Binaan Lapas - Muljanto Siladjaja; I Dewa Ketut Kerta Widana; Yohanes Ferry Cahaya; Herni Pujiati; Sri Yanthy Yosepha (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community development program aims to enhance the motivation and self-confidence of inmates at Cipinang Prison in order to break the cycle of poverty and prevent them from repeating past mistakes. The program involved 30 participants, most of whom were recidivists, facing the main challenge of negative social stigma that perceives former inmates as incapable of change. The solution introduced through the training was the utilization of household waste to produce eco enzyme products. These products have proven to be economically valuable and beneficial for health, thereby improving the living standards of inmates while simultaneously creating business opportunities. The simple and low-cost production process enabled participants to acquire new skills, while training on branding and packaging provided added value and increased product competitiveness in the market. Beyond empowering inmates, this program also contributes to environmental sustainability and promotes a healthy lifestyle at an affordable cost. The transformation of waste into health-supporting products demonstrates the wise use of natural resources and fosters entrepreneurial spirit among participants. Thus, this activity serves as an initial step in empowerment, expected to improve the quality of life and open better future opportunities for inmates.